Analisis Yuridis Terhadap Putusan yang Berakibat Pailitnya Suatu Perusahaan (Studi Kasus Putusan Pengadilan Negeri Gresik Nomor 1/PDT.SUS-PHI/2022/PN GSK) - Amelia, Sabina Putri; Widiastiwi, Alisha Reva; Camilla, Garneta Rizka; Tarina, Dwi Desi Yayi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Bankruptcy is a legal issue that has a broad impact on companies, creditors, and workers. In the context of civil law, bankruptcy occurs when a debtor is unable to fulfill his debt obligations that have matured and can be collected by creditors. This study focuses on a legal analysis of the Gresik District Court Decision Number 1/Pdt.Sus-PHI/2022/PN Gsk, which stated that PT New Era Rubberindo was bankrupt due to failure to pay workers' wages and holiday allowances (THR) within a certain period. This study uses a normative method with a case approach to evaluate the legal implications of the decision on workers' rights and the effectiveness of bankruptcy regulations in Indonesia. The results of the analysis show that bankruptcy not only has an impact on the sustainability of a company's business but also has significant consequences for the workforce. Based on Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations, workers' rights to salaries and allowances must be a top priority in the bankruptcy resolution process. In practice, the main obstacles that often arise are the slow process of resolving bankruptcy and the lack of clarity in the implementation of regulations that protect workers' rights. Therefore, more effective legal reform is needed to ensure a balance between the interests of creditors and the protection of workers' rights in the bankruptcy system in Indonesia.